Effects of paraffine oil on leaf and berry mycobiota on two grape varieties - Pálfi, Xénia; Karácsony, Zoltán; Kátai, János; Zsófi, Zsolt (Acta Agraria Debreceniensis, 2016)
Application of fungicides have advantages and also some direct or indirect disadvantages, such as imbalance and/or fungicide resistance in microbe population. To avoid these problems the development of alternative, eco-friendly methods like mostly spraying with oils are in the focus nowadays. The investigations of the effects of fungicides on microbiota in some cultivations can give a more complex view to this topic and developmental possibilities. In the present study, our aim was testing of the effects of paraffine oil (as alternative fungicide) on microbial properties (CFU and rate of filamentous fungi and yeasts) of Chardonnay and Kékfrankos leaves and berries.Our results from 2014 showed that the application of paraffine oil as sole spray agent can decrease the presence of saprophytic filamentous fungi on the berries of Chardonnay (susceptible for fungal infections). In the case of Kékfrankos berries opposite properties were observed, which may be the result of the absorption of oil by the thick wax layer of this variety. The oil treatment did not affect the yeast population of Chardonnay and Kékfrankos berries contrary to negative effect of the regular pesticide treatment. The selective fungicide effect of paraffine oil against filamentous fungal population caused the accumulation of yeast cells in the mycobiota of grape berries. The careful use of this yeasts in spontaneous fermentation can improve the aroma profile of wines. The year of 2015 did no prefer the growth of fungi, therefore no interesting properties were detected in the mycobiota of grape varieties. The occurence of the harmful saprophytic filamentous fungi predicted to be increased in mild climate agricultures as the result of the climate change.In summary, the paraffine oils are seem to be promising tools for the eco-friendly control of harmful fungi of grapes.